Reveal the Meaning of Gorontalo Local Wisdom in theImplementation of Accounting Education Based Culture - Amaliah, Tri Handayani; Noholo, Sahmin; Husain, Siti Pratiwi (International Journal of Multidisciplinary Applied and Science Research, 2025)
This paper aims to reveal the meaning of Gorontalo local wisdom in the implementation of accounting education based culture. Analysis unit in this research was concept of accounting education. Learning site was located in the Department of Accounting State University of Gorontalo. Data collection in this research performed through observation and interview. This research was qualitative research by using ethnomethodology as its analysis. The research result showed that Gorontalo local wisdom in the implementation of accounting education based culture means to inculcate religious values, realization of humanism values and moral awareness to the students. Based on the reality, meaning that found in this research could be stated that accounting education and learning should not only focus on thinking intelligence in accounting field, but also should be able to create accountant candidate with good characters. Thus, it needs efforts to integrate local wisdom values both in accounting course and in the teaching process. It was due to, actually, accounting curriculum contains cultural spirit of local wisdom